Follicular Dynamics and Fertility in Dairy Sheep: Influence of Progesterone and Reproductive Season - Brogni, Cláudio Francisco; Maicon Gaissler Lorena Pinto; Vilmar Francisco Zardo; Alceu Mezzalira (Acta Scientiae Veterinariae, 2024)
Background: The use of high and low doses of progesterone in vaginal pessaries directly interferes with the response of follicular dynamics in sheep specialized in dairy production. Within the season there is greater ovarian activity and outside the reproductive season the high dose of progesterone favors conception rates, the number of lambs born alive and the size of the gestational corpus luteum, which implies greater female fertility. This work evaluated the response of the follicular dynamics of dairy sheep inside and outside the reproductive season, during the 6 days of stay of the vaginal pessary containing high and low doses of progesterone. Materials, Methods & Results: The experiment was conducted within the reproductive season in April/May and outside the reproductive season in October/November, evaluating the ovarian response to the use of vaginal pessaries containing 60 or 120 mg of progesterone during 6 days of stay of the device. The dosage of 75 µg of sodium cloprostenol and 400 UI of equine chorionic gonadotropin (eCG) were applied at the time of removal of the pessaries and coverage with sheep occurred 50 h after removal of the device. As a result, it was observed that the ovulatory follicle has a larger diameter within the reproductive season at 5.95 mm and outside the season at 4.98 mm. The size of the dominant follicle at the beginning of the protocol (D0) was 4.77 mm inside the season versus 1.55 mm outside and without the presence of a corpus luteum, showing seasonal anestrus. The time of ovulation after removing the pessaries occurred around 48.68 h within the season and 53.40 h outside the reproductive season. Regarding the size of the corpus luteum (CL), it was larger during the breeding season with 12.15 mm compared to 11.45 mm outside the breeding season. For the conception rate inside the station, it was 71.4% and outside 50%. Outside the reproductive season, with a dose of 60 mg, the conception rate was 41.2% and with 120 mg, 58.8%. For the number of lambs born alive/ewe, within the breeding season it was found 2.32 and outside the season 1.59. Discussion: Seasonality in sheep is a notable factor, and during the off-season ovarian activity was in anestrus, with only small follicles without the presence of a corpus luteum. The in-station ovulatory follicle (OF) appeared at 3.79 days after device placement and out-of-station at 4.02 days. The possible explanation for this is the addition of progesterone from the intravaginal device associated with CL. The average ovulation period occurred around 48.68 h within the season, and outside the season this value was 53.40 h. This variation in sheep has already been described, but mapping in dairy sheep is the 1st study. The number of ovulations differed between the seasons evaluated and between doses of progesterone, which suggests a direct effect of dose and season on the number of ovulations. The conception rate at breeding time reached a much higher value, as ovarian activity and the presence of the CL on D0 make the female respond better to the protocol, a fact that can be observed with the greater size of the CL at 30 days. Outside the reproductive season, the 120 mg protocol resulted in a higher conception rate. This higher dose of progesterone better prepares the ovulatory wave of each cycle, providing better oocyte viability and, therefore, a higher conception rate in this period. Keywords: ovulation, follicular waves, ultrasonography, reproductive station, progesterone implants, seasonal anestrus. Título: Dinâmica folicular e fertilidade de ovelhas leiteiras: influência da progesterona e estação reprodutiva Descritores: ovulação, ondas foliculares, ultrassonografia, estação reprodutiva, implantes de progesterona, anestro sazonal.